Fabrication and Evaluation of Poloxamer Facilitated, Glyceryl Monooleate based 5-Fluorouracil Cubosomes - Alamoudi, Jawaher Abdullah; Almoshari, Yosif; Alotaibi, Hadil Faris (Indian Journal of Pharmaceutical Education and Research, 2024)
Objectives: This study aims to prepare a topical cubosomal formulation that contains 5-Fluorouracil (5-FU), a hydrophilic anti-cancer drug, that belongs to the Biopharmaceutics Classification System (BCS-III) i.e., high solubility and low permeability. Materials and Methods: The 5-FU loaded cubosomes were prepared using Glyceryl Monooleate (GMO) as a lipid polymer, in the presence of Poloxamer 407 (Polox-407) and Tween 80 (T80) as stabilizers. Four formulations of cubosomes were formulated by varying concentrations of Polox-407 and GMO while keeping the concentration of T80 constant. A melting, followed by homogenization technique has been used for the preparation of 5-FU cubosomes. Several In vitro characterization experiments, chemical compatibility studies, pH, viscosity, Scanning Electron Microscopy (SEM), particle size analysis, zeta potential, in vitro drug release studies, in vitro permeation study, and stability studies were performed. Results: The compatibility studies have confirmed the chemical compatibility of the drug and ingredients, while stability analysis has assured that the prepared formulations were stable. Particle size analysis and surface morphology showed that particles were nano-sized with suitable cubical shapes, well segregated from each other. The zeta potential was -0.6 mV and viscosity has been recorded as 18 cP. The drug release and permeation studies revealed that the cumulative amount of the drug was 95% and 94% respectively. Conclusion: Altogether, these findings suggested that upon further optimization, this formulation may have the potential to be translated as an effective therapy for the clinical management of superficial cancers.
Keywords: Cubosomes; Permeation; Drug release; Thermal analysis